ASUHAN KEPERAWATAN PADA LAKI-LAKI DEWASA DENGAN DIAGNOSA TUBERCULOSIS PARU - astri doris (Akper Kesdam I/Bukit Barisan Padang, 2019)
Tuberculosis is a disease caused by Mycobacterium tuberculosis, usually affecting the lungs, which can then occur in all parts of the body. Infection usually occurs in 2-10 weeks. After 10 weeks, the client will manifest disease manifestations due to impaired and ineffective immune response. The aim of this literature study was to conduct a literature study explored the management of nursing care with pulmonary tuberculosis in adult males. This research design was prepared using a descriptive method approach. The data method used in this research is the documentation method. Based on the results of the assessment, it was found that Mr. P. had pulmonary tuberculosis with complaints of chest pain, shortness of breath, Mr. P. was suffering from pulmonary tuberculosis for the first time but suffered from a typical clinical manifestation in Taktem clients to Taktem clients.